Enhancing accessibility of higher education through the system of educational credits - Shamil Z, Valiev,; Talipova, Aida Kh (Opción, 2019)
The aim of the study is to investigate enhancing accessibility of higher education through the system of educational credits. The methodological basis of the present research were theories, doctrines and approaches of scientists, studying the problem of educational crediting and accessibility of higher education. In result, the model of the educational crediting system with the state support consists of three blocs: the bloc of agreement (№1), the organizational-functional bloc (№2), the receiving credit bloc (№3). In conclusion, these blocs enable us to determine the functions and responsibility of each system structure.